Rating of community colleges for their role in obtaining undergraduate degrees - Luán, Jing (Journal of International Students, 2026)
University rankings exert significant influence over student choice, institutional behavior, and global perceptions of educational quality. However, prevailing ranking systems rely on narrow, prestige-driven indicators that misrepresent institutional effectiveness, reinforce inequality, and marginalize mission-sensitive sectors of higher education. Among the most affected are U.S. community colleges, which play a critical role in undergraduate degree attainment, workforce development, and social mobility but remain largely absent from national and global evaluative frameworks. This paper argues that traditional ranked-order systems are conceptually and methodologically inappropriate for assessing community colleges. Instead, it proposes a multidimensional rating framework that clusters institutions by mission-sensitive variables. Drawing on AI data mining and unsupervised machine learning techniques, the article introduces a cluster-based approach to evaluate community colleges across key dimensions, including transfer outcomes, institutional support capacity, and geographic context. Using University Transfer Admission (UTA) as a demonstrative case, the study illustrates how clustering enables context-sensitive, student-centered decision-making without imposing artificial hierarchies. The proposed framework offers a more equitable, transparent, and analytically sound alternative to conventional rankings, supporting informed choice, policy development, and institutional accountability while recognizing the diverse missions of community colleges. It will have broad utility for other institutions.